2013
DOI: 10.1186/gb-2013-14-5-r42
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal, genome-scale analysis of DNA methylation in twins from birth to 18 months of age reveals rapid epigenetic change in early life and pair-specific effects of discordance

Abstract: BackgroundThe extent to which development- and age-associated epigenetic changes are influenced by genetic, environmental and stochastic factors remains to be discovered. Twins provide an ideal model with which to investigate these influences but previous cross-sectional twin studies provide contradictory evidence of within-pair epigenetic drift over time. Longitudinal twin studies can potentially address this discrepancy.ResultsIn a pilot, genome-scale study of DNA from buccal epithelium, a relatively homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(177 citation statements)
references
References 85 publications
8
169
0
Order By: Relevance
“…It is therefore plausible that gene promoters undergoing age-associated epigenetic drift should be of typically lower degree, as otherwise induced changes in gene expression at hubs could likely compromise essential cellular functions. For instance, a number of recent studies have shown that epigenetic drift is detectable even in pediatric populations (i.e., well before the reproductive period) (43,49) and that DNAm patterns in newborns are correlated with maternal age (50), suggesting that a fraction of the changes caused by epigenetic drift may be heritable. Thus, if age-associated epigenetic drift kicks in straight after birth-that is, well before the reproductive periodit is then entirely plausible that natural selection would weed out any age-associated epigenetic silencing of integral housekeeping genes, including for instance those involved in embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore plausible that gene promoters undergoing age-associated epigenetic drift should be of typically lower degree, as otherwise induced changes in gene expression at hubs could likely compromise essential cellular functions. For instance, a number of recent studies have shown that epigenetic drift is detectable even in pediatric populations (i.e., well before the reproductive period) (43,49) and that DNAm patterns in newborns are correlated with maternal age (50), suggesting that a fraction of the changes caused by epigenetic drift may be heritable. Thus, if age-associated epigenetic drift kicks in straight after birth-that is, well before the reproductive periodit is then entirely plausible that natural selection would weed out any age-associated epigenetic silencing of integral housekeeping genes, including for instance those involved in embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These changes occur preferentially at CpG island shores and shelves, enhancers, and promoters lacking CpG islands (McClay et al ., 2014). In both blood and buccal epithelial cells, DNA methylation between monozygotic twins has been shown to become more variable in the first year of life (Martino et al ., 2011, 2013). This phenomenon may indicate that the shared prenatal environment confers a high degree of epigenetic similarity between children, whereas subsequent variations in the postnatal environment result in epigenetic divergence after birth.…”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
“…Further evidence for genetic contributions to epigenetic aging come from studies examining age and DNA methylation that have also observed high correlation of DNA methylation levels between twins at more than one age (Bell et al ., 2012; Martino et al ., 2013). Similar studies in adults have shown greater concordance in DNA methylation profiles between monozygotic twins than dizygotic twins (Kaminsky et al ., 2009; Bell et al ., 2011).…”
Section: Considerations For Studies Of Epigenetics and Agingmentioning
confidence: 99%
“…16 Buccal samples used in this study were selected based on the availability of the materials and array data quality. Data from dried blood spots used in this study were from a case/control study of DNA methylation associated with preterm birth.…”
Section: Samples Used In This Studymentioning
confidence: 99%